Comparison of corn and milo grain in fattening ration of beef cattle-Summary. - Richardson, D.; Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2011)
Kansas is surpassed only by Texas in total sorghum acreage and production. A large part of this acreage consists of the type that has a short stalk and is, therefore, suitable for harvesting the grain with a combine. This means that there is a large amount of the grain available for feeding livestock. This experiment was planned to study the relative value of corn and milo grain in the fattening ration of beef cattle. Rate of gain, feed consumption, economy of gain, dressing percentage, carcass grade, and degree of marbling were used to make comparisons.
Keywords: Beef; Corn; Milo